miRNA-191 and miRNA-548c-3p Expression in Embryo Culture Medium and Their Association with Chromosomal Status - Riyan Hari Kurniawan; Raden Muharam Natadisastra; Indah Suci Widyahening; Pritta Ameilia Iffanolida; Budi Wiweko (Indonesian Socety of Obstetrics and Gynecology, 2026)
Objective: To analyze the relationship between the expression levels of miRNA-191 and miRNA-548c-3p in embryo culture media and embryo chromosomal status. Methods: This cross-sectional study was conducted on 30 embryos from 12 patients aged 28–40 years who underwent an in vitro fertilization (IVF) program in three clinics. Embryos were cultured until the blastocyst stage. PGT-A was performed after blastocyst biopsy on day 5 or 6, and chromosomal analysis was carried out using the NGS method. The expression levels of miRNA-191 and miRNA-548c-3p were analyzed from embryo culture media samples using the qPCR method. The relationship between the expression levels of these miRNAs and embryo chromosomal status was then assessed. Results: There were no significant differences in subjects’ characteristics between the euploid and aneuploid embryo groups (p > 0.05). There was no significant difference in the expression level of miRNA-191 between euploid and aneuploid embryos (median quantification 7.260 vs 1.039, p = 0.497). Similarly, there was no significant difference in the expression level of miRNA-548c-3p between the two groups (median quantification 1.919 vs 4.311, p = 0.707). Conclusion: The expression levels of miRNA-191 and miRNA-548c-3p show no relationship with embryo chromosomal status. Their expression in embryo culture media does not appear to be a good biomarker candidate for predicting embryo chromosomal status. Keywords: Chromosomal status, IVF, miRNA-191, miRNA-548c-3p.